Mengukur Keterlibatan Pelanggan pada Niat Pembelian Online dengan Pendekatan Mediasi di Aplikasi Shopee di Medan - Romindo M Pasaribu; Agnes Frengky Zai; Hanna M Damanik; Vinsensius Matondang (Universitas 17 Agustus 1945 Semarang, 2024)
This study aimed to assess the impact of cognitive involvement, affective involvement, and customer behavioral involvement on online purchase intentions, with customer experience as a mediator on the Shopee application in Medan City. The research included 130 respondents from Medan City, selected using purposive sampling. Data analysis was conducted using the SMARTPLS version 3.0 program, employing Structural Equation Modeling (SEM), measurement models (outer models), structural measurements (inner models), and hypothesis testing. The results indicated that customer cognitive involvement had a positive but insignificant effect on customer experience. Affective and behavioral involvement had a positive and significant effect on customer experience. Both cognitive and behavioral involvement had a positive and significant effect on online purchase intentions, while customer affective involvement had a positive but insignificant effect on online purchase intentions. Furthermore, customer experience had a positive and significant effect on online purchasing intentions. It was found that customer experience was unable to mediate the influence of customer involvement on online purchasing intentions. However, customer experience was able to mediate the influence of affective and behavioral customer involvement on online purchasing intentions. Hence, businesses using the Shopee application can enhance customer engagement and leverage technological advancements to attract purchasing intentions by introducing additional features with creativity and openness.